Self-assembly of isomeric naphthalene appended glucono derivatives: nanofibers and nanotwists with circularly polarized luminescence emission. Issue 17 (20th March 2020) - Liu, Zongwen; Jiang, Yuqian; Jiang, Jian; Zhai, Donghua; Wang, Decai; Liu, Minghua
Abstract : Two isomers of naphthalene derivatives are self-assembled into nanofibers and nanotwists with CPL emission, respectively. Abstract : Two isomeric naphthalene appended glucono derivatives substituted at the 1 or 2-naphthyl positions (Nap-1 and Nap-2 ) were designed and their self-assembly behaviors and optical properties were investigated. Nap-1 and Nap-2 were found to self-assemble into nanofibers and nanotwists, respectively. While the molecular chirality of the glucono moiety could not be effectively transferred to the naphthalene moiety in the Nap-1 system, this was achieved in the Nap-2 assembly. Thus, the Nap-2 assembly showed obvious circular dichroism (CD) and circularly polarized luminescence (CPL) signals. From the XRD patterns and IR spectra of the supramolecular assemblies, it was found that Nap-2 packed in a more orderly fashion than Nap-1, leading to a hierarchical assembly forming nanotwist structures. Moreover, a light-harvesting system based on Nap-2 supramolecular gels and dyes was established, in which an efficient energy transfer was demonstrated from Nap-2 to an acceptor Eosin Y. It was further found that both chirality and energy transfer enhanced the dissymmetry factor of Eosin Y CPL emission.